2020
DOI: 10.18632/oncotarget.27693
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed full-length, fusion and novel isoforms transcripts-based signature of well-differentiated keratinized oral squamous cell carcinoma

Abstract: Highly keratinized oral squamous cell carcinoma (OSCC) exhibits an improved response to treatment and prognosis compared with weakly keratinized OSCC. Therefore, we aimed to develop gene transcript signature and to identify novel full-length isoforms, fusion transcript and non-coding RNA to differentiate welldifferentiated (WD) with Moderately Differentiated (MD)/Poorly Differentiated (PD)/WD-lymphadenopathy OSCC through, HTA, Isoform sequencing, and NanoString. Additionally, specific copy number gain and loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The RBPJ, SPAG7, and ESRRA TFs were all highly expressed in AK compared with NS as a whole (Figure S4F), which was in accordance with the role they played in the development of SCC. [23][24][25] Moreover, they were more highly expressed in clusters 9 and 11 (Figure S4E). These results suggested that specific regulons were active in AK-specific keratinocytes whose activity differed between AK clusters, reinforcing the heterogeneity of AK, which might be important in AK biology.…”
Section: Transcriptional Heterogeneity Controlled By Tf Regulators In Akmentioning
confidence: 96%
“…The RBPJ, SPAG7, and ESRRA TFs were all highly expressed in AK compared with NS as a whole (Figure S4F), which was in accordance with the role they played in the development of SCC. [23][24][25] Moreover, they were more highly expressed in clusters 9 and 11 (Figure S4E). These results suggested that specific regulons were active in AK-specific keratinocytes whose activity differed between AK clusters, reinforcing the heterogeneity of AK, which might be important in AK biology.…”
Section: Transcriptional Heterogeneity Controlled By Tf Regulators In Akmentioning
confidence: 96%
“…Overall, epidermis and mucosa undergo to tissue-specific mechanical stress and exposure to environmental stimuli, including contacts with secretes (such as mucus) and enzymes characteristic of the tissue, as well as pathogens. Furthermore, with regard to keratin expression in neoplastic versus healthy tissues, both proteomic and transcriptomic profiles reveal the presence of a tumor dependent signatures, with a defined keratin pattern associated with proliferation and differentiation status of the cells ( 34 36 ). For example, while Keratin 13 is absent in cancers from the gingivo-buccal complex ( 35 ), it becomes indicative of a neoplastic and malignant conversion in skin cancers ( 37 – 39 ).…”
Section: Oral Versus Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%
“…We performed microarray assay on 10 NSCLC stage IIIA and 5 control samples to establish gene-expression profiles using GeneChip® Human Transcriptome Array 2.0 (HTA 2.0, Affymetrix, Santa Clara). 10 We measured the RNA concentrations with the Qubit 3.0 Fluorometer (Invitrogen, USA). We processed 500ng RNA samples with the WT PLUS Reagent kit, followed by hybridization on the HTA 2.0 microarray chips.…”
Section: Human Transcriptome Array 20 Hybridizationmentioning
confidence: 99%
“…NanoString geneexpression analysis was performed as previously done. 10 In brief, hybridization of 100 ng of total RNA with customized reporter code set (for gene-transcript expression or gene fusion-transcript) and capture probe set was performed in a NanoString Prep Station (NanoString Technologies), and the mRNA molecules counted with the NanoString nCounter (NanoString Technologies). The nSolver™ Analysis Software 3.0 (NanoString Technologies) was used to perform data handling, including automated background subtraction, spike-in-control normalization, and reference gene normalization.…”
Section: Ncounter-based Gene-expression Validationmentioning
confidence: 99%